2016
DOI: 10.1364/boe.7.001400
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing spatial correlations in tissue using angle-resolved low coherence interferometry measurements guided by co-located optical coherence tomography

Abstract: Angle-resolved low coherence interferometry (a/LCI) is an optical technique used to measure nuclear morphology in situ. However, a/LCI is not an imaging modality and can produce ambiguous results when the measurements are not properly oriented to the tissue architecture. Here we present a 2D a/LCI system which incorporates optical coherence tomography imaging to guide the measurements. System design and characterization are presented, along with example cases which demonstrate the utility of the combined measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Before imaging, each eye was cleared of connective tissue and the superior quadrant was marked. The eye was then positioned with the superior quadrant aligned with the positive vertical scan axis in a custom-designed chamber and stabilized with grease 37 . The chamber design accounted for the eye curvature, which maintained its alignment relative to the custom objective during imaging.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Before imaging, each eye was cleared of connective tissue and the superior quadrant was marked. The eye was then positioned with the superior quadrant aligned with the positive vertical scan axis in a custom-designed chamber and stabilized with grease 37 . The chamber design accounted for the eye curvature, which maintained its alignment relative to the custom objective during imaging.…”
Section: Sample Preparationmentioning
confidence: 99%
“…a/ LCI is an optical technique which detects depth-resolved angular scattering distributions from tissue, and has demonstrated high clinical diagnostic accuracy in Barrett's esophagus 35 and cervical dysplasia 36 . Although a/ LCI is not itself an imaging modality, it can be combined with the image guidance of OCT to extract unique light scattering features from distinct layers of the retinal tissue 37 . Co-registration of OCT and a/LCI to an identical imaging volume yields complementary information, specifically by allowing localization of regions of interest in the retina, followed by a/LCI analysis of light scattering parameters.…”
mentioning
confidence: 99%
“…Angle-resolved OCT is a subset of OCT that provides multiple signals that are sensitive to the angle of light backscattered from the specimen. [36][37][38] A variety of angle-resolved techniques have demonstrated the utility of incorporating angular backscattering information into the OCT signal, including multidirectional OCT for retinal imaging, 39 bright-and dark-field imaging with few-mode fibers for angular multiplexing, 40 and directional OCT for imaging melanin concentration. 41 A specific subtype of angle-resolved OCT, termed scattering-angle-resolved OCT (SAR-OCT), positions an optical element in the pupil of the scanning system that pathlength-encodes angular information of backscattered light from the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, angle-resolved interferometric imaging approaches have been used to detect sub-wavelength cellular properties such as the size distribution of nuclei and more recently to characterize nuclear morphology, in situ, of both a rodent model for esophageal carcinogenesis and murine retinas [8,9]. Thus, while several cell culture and ex-vivo tissue studies have been reported involving angle-resolved imaging, similar optical imaging techniques have not been extensively explored for retinal imaging.…”
Section: Introductionmentioning
confidence: 99%